FEATURES OF APPLICATION OF METHODS OF NETWORK PLANNING AT PROJECT MANAGEMENT AT THE ENTERPRISES OF MECHANICAL ENGINEERING - L. Mikhailova; A. Sazonov; D. Petrov (Вестник университета, 2017)
In article it is proved that one of the methods which are most often applied in planning of production activity of the enterprises of mechanical engineering are methods of network planning. As the production program of machine-building enterprise in most cases consists of a number of the projects interconnected with each other, the realization of such program can be enabled by means of a method of the chart of Gant. Authors have presented an algorithm and an example of creation of the chart.